The Influence of Window Openings on the Energy Efficiency of Office Buildings - Vidmar, Rangel Girardelo; Cunha, Eduardo Grala da; Ribeiro, Lauro André; Silva, Thaísa Leal da (Technical and Scientific Journal Green Cities, 2024)
The construction sector is responsible for a significant portion of energy consumption and greenhouse gas emissions. Therefore, it is crucial to develop initiatives that identify and reduce energy consumption in buildings from the planning stage, contributing to the sustainability of these constructions. In this context, this study aims to examine the influence of window opening size in a model of an office building located in Passo Fundo, RS, in Bioclimatic Zone 2 (ZB2). To this end, six computer simulations were performed using Energy Plus software in a model of an office building, considering windows occupying 25%, 50% and 100% of the building's façade size. Tests were also performed using single and double glazing. The results revealed that the larger the window opening, the greater the energy consumption to maintain thermal comfort in the environment, representing an increase of 11.36% in consumption for the case with 100% window opening compared to the case with 25% opening. Thus, the size of the window opening has a significant impact on the energy consumption of the office building model analyzed.
Keywords: Thermal performance; Greenhouse buildings; Computer simulation; Opening windows